2014
DOI: 10.3389/fchem.2014.00054
|View full text |Cite
|
Sign up to set email alerts
|

Bis-indole derivatives with antitumor activity turn out to be specific ligands of human telomeric G-quadruplex

Abstract: Bis-indolinone derivatives having either 2,6-disubstituted pyridine core (1a and 1b) or 1,10-disubstituted phenanthroline core (2a and 2b), already known to have antitumor activity, have been tested as potential G-quadruplex binders. Compounds 2a and 2b are able to selectively stabilize G-quadruplex over duplex DNA, and also to discriminate among different G-quadruplex structures, having a particular affinity for the parallel form of the human telomeric G-quadruplex. Both compounds are also able to induce telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…As it appears that formation of iM and/or G4 structures could incite different biological outcomes, it is important to understand the potential structures a compound is able to interact with. In contrast to the hundreds of G4 binding ligands (Pagano et al, 2007 , 2010 , 2015 ; Di Leva et al, 2013 ; Li et al, 2013 ; Amato et al, 2014a , 2018 ), there are comparatively very few iM binding compounds reported in the literature (Day et al, 2014 ). Some ligands which were described to bind G4 have also been found to bind iM (Fedoroff et al, 2000 ; Wright et al, 2016a ; Xu et al, 2016 ), so we decided to assess and compare the capability to interact with iM-forming DNA of several known bioactive G4 binding agents: Berberine ( 1 ) (Franceschin et al, 2006 ), BRACO-19 ( 2 ) (Gowan et al, 2002 ), Mitoxantrone ( 3 ) (Huang et al, 2007 ), Phen-DC3 ( 4 ) (De Cian et al, 2007a ), Pyridostatin ( 5 ) (Rodriguez et al, 2008 ), and RHPS4 ( 6 ) (Izbicka et al, 1999 ) (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As it appears that formation of iM and/or G4 structures could incite different biological outcomes, it is important to understand the potential structures a compound is able to interact with. In contrast to the hundreds of G4 binding ligands (Pagano et al, 2007 , 2010 , 2015 ; Di Leva et al, 2013 ; Li et al, 2013 ; Amato et al, 2014a , 2018 ), there are comparatively very few iM binding compounds reported in the literature (Day et al, 2014 ). Some ligands which were described to bind G4 have also been found to bind iM (Fedoroff et al, 2000 ; Wright et al, 2016a ; Xu et al, 2016 ), so we decided to assess and compare the capability to interact with iM-forming DNA of several known bioactive G4 binding agents: Berberine ( 1 ) (Franceschin et al, 2006 ), BRACO-19 ( 2 ) (Gowan et al, 2002 ), Mitoxantrone ( 3 ) (Huang et al, 2007 ), Phen-DC3 ( 4 ) (De Cian et al, 2007a ), Pyridostatin ( 5 ) (Rodriguez et al, 2008 ), and RHPS4 ( 6 ) (Izbicka et al, 1999 ) (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of small heterocyclic molecules have been synthesized and evaluated for their ability to interact with G‐quadruplexes . Among them are the 1,10‐phenanthroline derivatives, such as PhenDC3 and its structural analogues I , tetraaminophenanthroline II , K35, and phenanthroline‐2,9‐bistriazole III (Figure ) . These compounds have been investigated for their capacity to bind and stabilize various G4 topologies and for their selectivity for G‐quadruplex versus duplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Several organic molecules have been shown to be able to bind and stabilize BCL2 ‐G4 with subsequent down‐regulation of Bcl‐2 transcription and expression levels, thereby demonstrating the real potential of the G‐quadruplex‐targeting therapeutic approach, which also has the great advantage of circumventing the problem of acquired resistance, which is the main limitation of current Bcl‐2‐targeted therapeutic strategies. Most of the BCL2 ‐G4 ligands identified so far are characterized by a large, planar aromatic core with the capability of stacking on the external G‐tetrads, a common element in G‐quadruplex recognition . Therefore, although these ligands have shown good G‐quadruplex over duplex selectivity, they do not exhibit specificity for BCL2 ‐G4 versus other G‐quadruplex structures.…”
Section: Figurementioning
confidence: 99%